2021
DOI: 10.7554/elife.63502
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal high-throughput TCR repertoire profiling reveals the dynamics of T-cell memory formation after mild COVID-19 infection

Abstract: COVID-19 is a global pandemic caused by the SARS-CoV-2 coronavirus. T cells play a key role in the adaptive antiviral immune response by killing infected cells and facilitating the selection of virus-specific antibodies. However, neither the dynamics and cross-reactivity of the SARS-CoV-2-specific T-cell response nor the diversity of resulting immune memory is well understood. In this study, we use longitudinal high-throughput T-cell receptor (TCR) sequencing to track changes in the T-cell repertoire following… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(153 citation statements)
references
References 44 publications
3
149
0
1
Order By: Relevance
“…Activated CD8 + T cells can directly kill infected cells, while CD4 + T cells can drive and help CD8 + T cell responses and participate in the process of antigen-specific B cells producing neutralizing antibodies. 27 Therefore, we first analyzed the ability of RBD-BBVs to induce CD4 + T and CD8 + T cell responses. The experimental results showed that RBD-BBVs induced CD4 + T ( Figure 5 F) and CD8 + T ( Figure 5 G) responses.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Activated CD8 + T cells can directly kill infected cells, while CD4 + T cells can drive and help CD8 + T cell responses and participate in the process of antigen-specific B cells producing neutralizing antibodies. 27 Therefore, we first analyzed the ability of RBD-BBVs to induce CD4 + T and CD8 + T cell responses. The experimental results showed that RBD-BBVs induced CD4 + T ( Figure 5 F) and CD8 + T ( Figure 5 G) responses.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We also discovered T cells cross-reactive for SARS-CoV-2 and common cold coronavirus variants of an HLA*B15-restricted immunodominant epitope. The possibility of this cross-reactivity was hypothesized in (Minervina et al 2021), where the clonotypes with this TCR motif were the most expanded in an HLA-B*15 positive donor. Francis et al recently described HLA-B*07_SPR, another epitope from N-protein, as being cross-reactive with HKU1 and OC43 common-cold coronaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…TCRα (TRAV21, CAVHSSGTYKYIF, TRAJ40) and TCRβ (TRBV7-2, CASSLEDTNYGYTF, TRBJ1-2) chains matching both the biggest B15_NQK-specific motif on Fig 4B and prediction from (Minervina et al 2021) were selected for Jurkat cell line generation. TCRα and TCRβ chains for the selected B15_NQK-specific TCR were modified to use murine constant regions (murine TRAC*01 and murine TRBC2*01).…”
Section: Tcr-expressing Jurkat 767 Cellsmentioning
confidence: 99%
“…Recent progress has already brought the cost and turnaround time of AIRR-seq tests within range of other clinical NGS tests, especially those that must be performed at reference laboratories, also known as "send-out tests" (as opposed to tests that can be performed on site at the hospital). Most critically, sequencing has the fundamental advantage of being an unbiased method, which can in principle reveal atypical immune responses, or responses to new or emerging pathogens such as SARS-CoV-2 without the cost and delay required to develop new pathogen-specific reagents (42)(43)(44). Regardless of the condition, the sequencing procedure is the same; what differs is the computational query for each test result: one for influenza, another for lupus, and so on.…”
Section: Advantages Of Airr-seqmentioning
confidence: 99%